2008
DOI: 10.12968/ijtr.2008.15.6.29878
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver stress in traumatic brain injury

Abstract: Aims: Many patients experience physical, behavioural, cognitive and emotional problems following traumatic brain injury (TBI). They may require continuing care for many years, most of which is provided by informal caregivers, such as spouses, parents, or other family members. The caregiving role is associated with a range of adverse effects including anxiety, depression, poor physical health and lowered quality of life. This article explores issues around caregiver stress; highlighting interventions for this g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 71 publications
3
22
0
3
Order By: Relevance
“…Caregivers' support needs can be viewed as a spectrum of needs, including practical, spiritual, psychosocial, informational, emotional, and physical support needs, as adapted from the supportive care needs framework model for caregivers of cancer patients (Fitch, 1994). A number of studies have shown that the need for information is a top priority among caregivers of persons with dementia (Muangpaisan et al, 2010;Wackerbarth & Johnson, 2002), stroke (Hare, Rogers, Lester, McManus, & Mant, 2006;Kim & Moon, 2007;MacIsaac, Harrison, & Godfrey, 2010;Mak, Mackenzie, & Lui, 2007;), spinal cord injury (SCI; Meade, Taylor, Kreutzer, Marwitz, & Thomas, 2004;Post, Bloemen, & de Witte, 2005), traumatic brain injury (TBI; Arango-Lasprilla et al, 2010;Blake, 2008, Rotundi, Sinkule, & Spring, 2005Sander, Clark, Atchison, & Rueda, 2009), Parkinson's disease (PD; Hasson et al, 2010;Kristjanson, Aoun, & Oldham, 2006;Thomas & Sweetnam, 2002), and multiple sclerosis (MS; Corry & While, 2009;Kersten et al, 2000;Koopman, Benbow, & Vandervoort, 2006;Kristjanson et al, 2006). In general, caregivers of persons with chronic disease have been shown to desire two types of information: general information about the medical condition of the care recipient and specific, understandable information tailored to their situation.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers' support needs can be viewed as a spectrum of needs, including practical, spiritual, psychosocial, informational, emotional, and physical support needs, as adapted from the supportive care needs framework model for caregivers of cancer patients (Fitch, 1994). A number of studies have shown that the need for information is a top priority among caregivers of persons with dementia (Muangpaisan et al, 2010;Wackerbarth & Johnson, 2002), stroke (Hare, Rogers, Lester, McManus, & Mant, 2006;Kim & Moon, 2007;MacIsaac, Harrison, & Godfrey, 2010;Mak, Mackenzie, & Lui, 2007;), spinal cord injury (SCI; Meade, Taylor, Kreutzer, Marwitz, & Thomas, 2004;Post, Bloemen, & de Witte, 2005), traumatic brain injury (TBI; Arango-Lasprilla et al, 2010;Blake, 2008, Rotundi, Sinkule, & Spring, 2005Sander, Clark, Atchison, & Rueda, 2009), Parkinson's disease (PD; Hasson et al, 2010;Kristjanson, Aoun, & Oldham, 2006;Thomas & Sweetnam, 2002), and multiple sclerosis (MS; Corry & While, 2009;Kersten et al, 2000;Koopman, Benbow, & Vandervoort, 2006;Kristjanson et al, 2006). In general, caregivers of persons with chronic disease have been shown to desire two types of information: general information about the medical condition of the care recipient and specific, understandable information tailored to their situation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, caregivers play an important role in helping them to go through the abovementioned processes (1,5,6,(9)(10)(11)15).Effective adjustment to these difficult consequences enables survivors to recover from disability, gain increased independence and improve their quality of life (27).…”
Section: Discussionmentioning
confidence: 99%
“…How caregivers cope can adversely affect the status of their health (1,11,14,18).As for their health problems, emotional functioning, mental and physical health, many studies (29)(30)(31)(32) clearly note correlations with the recovery outcomes of survivors with TBI in the rehabilitation phase. However, the caregivers in this study reported more problems with physical health than emotional functioning and mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers experience elevated levels of depression and anxiety after a neurological event in their loved ones (see Blake 2008, for a review; Harris et al 2001;Hoofien et al 2001;Judd 1999;Kreutzer et al 1994;Marsh et al , 2002Schonberger et al 2010;Turner et al 2010). As identified in phase 1 of the FEM, relatives react with panic upon notification of their loved one's injury, in combination with dread that their loved one may not survive McAlaster et al 2004).…”
Section: Depression Anxiety and Demoralizationmentioning
confidence: 99%